Evaluation of the Level of Lysyle Oxidase and Some Biochemical Parameters in People with Glaucoma - hussin, Abdullah najm abdullah; AL-SADOON, Mohammed B. (American Journal of Biomedicine and Pharmacy, 2025)
The study sought to quantify a few biochemical factors in glaucoma patients' blood serum. A significant increase in the activity of the lysyl oxidase like -4 (LOXL-4) enzyme in patients' blood serum who have gluacoma of both genders was found statistical significance (p≤0.01) in the study, which involved 90 healthy and glaucoma patients (ages 50–83). Additionally, by assessing twelve oxidation and antioxidant variables as well as enzyme activity, it sought to compare the effects of oxidative stress on gluacoma patients to those in good condition. In contrast to those in good health, the findings showed a substantial increase in the activity of the LOXL-4 enzyme, malondialdehyde, lipoxygenase, and (TNF-a) at the p-value (p≤0.01*). Additionally, because of the increased oxidative stress, the data showed that all antioxidants (vit C, vit D, albumin, glutathione, glutathione peroxidase, ceruloplasmin , zinc) were significantly lower in glaucoma patients than in healthy individuals. Gender's impact was also examined.